Citius, Altius, Fortius in a deregulated labour market: narratives of precarious graduates. (1st April 2017) - ,; ,
Abstract : Labour markets foster qualification models and professionalisation strategies characterised by insecurity and deregulation. This article analyses narratives of precarious graduates through a subject-oriented approach, taking into account the increasing vulnerability, insecurity and fragmentation that characterise the professional experiences of graduates in the current global economic and financial crisis. Drawing upon information-rich evidence from 21 focus group interviews carried out in a research project in Portugal, this article aims to highlight how young graduates are experiencing, interpreting and managing dilemmas in their transitions from higher education into the labour market. It concludes that ambivalent and unpredictable paths have become the 'main route' for accessing a profession in a context of precariousness.